The economic impact of COVID-19 - Hudd, Emily (Core Library guide to COVID-19., 2021)
Explores the economic downturn that occurred during the COVID-19 pandemic in 2020, discussing how government mandates to close schools and businesses cost people their jobs and livelihoods. Discusses ways the government and people themselves tried to help one another through this economic crisis. Includes a glossary.